Association between Gallstones and Diabetics Type 2 Iraqi Patients - Anmar H. Altaie (College of Pharmacy University of Baghdad, 2017)
Gallstone disease is one of the most common complications among diabetic patients especially type 2 DM. Till now, there is no specific and certain factor that explain the incidence of gallstones among type 2 diabetic patients and many risk factors are taken collectively to estimate its intensity and severity compared to non diabetic counter parts. This clinical study was designed to evaluate and report the incidence and severity of gallstones among type 2 diabetics and non diabetics regarding certain factors. 20 diabetic females and 20 diabetic males were collected as patients′ group and have had gallstones while 20 females and 20 males who have had gallstones without diabetes mellitus type 2 were collected as controls′ group. The age, weight, and both of the size and number of gallstones of diabetic patients and controls were correlated to demonstrate the prevalence of gallstones among the patients′ and controls′ groups. The study showed that the mean ages of female patients is slightly higher (p<0.05) than the female controls. On the other hand there was a significant difference (p<0.05) between female and male control subjects. The body mass index (BMI) of male patients was significantly higher (p<0.05) than the male controls, while there was a significant difference (p<0.05) between female and male control subjects. The results of the study presented that the stone size of female patients was significantly higher (p<0.05) than the female and male controls, while the stone diameter of male patients was significantly higher (p<0.05) than the male and female controls. The stone number of female patients was significantly higher (p<0.05) than the female and male controls, while the stone number of male patients was significantly higher (p<0.05) than the male and female controls. These findings suggest that the incidence of gallstones was higher in type 2 diabetics both in males and females than the non diabetics and more in females than males who were non diabetics. Key words: Diabetes mellitus, gallstones, gender, ultrasound